Atividades didáticas para o ensino de computação na pré-escola - Martins, Everton Carlos (2020)
In the 21st century, various activities involve the use of or depend on computer technologies to exist. In this scenario, although children are surrounded by computing, many are still passive users, that is, they do not understand the computational solutions they use and do not use their potential to solve real problems. This problem is aggravated by children of preschool age, that is, 4 to 5 years in Brazil. What is clear is that, although children are exposed to computational solutions, preschool teachers are still discouraged from teaching content related to computers and technology for children, as they consider complex and unrelated to basic curricula and also due to the lack of plans that serve as pedagogical support for the application of activities in the classroom. Thus, in order to help overcome these barriers, the objective of this research is to propose and evaluate a set of activities that offer methodological didactic support so that preschool teachers can work independently on the elementary and preliminary concepts related to the knowledge of computing for children aged 4 to 5 years. To this end, the methodological approach of this research was divided into two stages: (1) used the focus group method with 6 professionals in computing and education to develop 14 lesson plans of didactic activities that addressed content related to data storage and processing, the 4 competencies of computational thinking, the approach to teaching unplugged (without the use of technologies) and, finally, linked to the axes and competencies of the Common National Curricular Base. (2) used the survey method with 113 professionals linked to preschoolers and pedagogy students to evaluate the lesson plans of the didactic activities proposed by this research using the online questionnaire technique. According to the data analysis, considering the total of 339 evaluations received from the lesson plans for each aspect of the rubric used and adapted for this research, obtained an average positive result greater than 90%. Furthermore, considering the comments to the open and non-mandatory question and the interest of the evaluators (96.5%) in applying the activities developed in the classroom after a post-pandemic scenario, the results suggest that the hypothesis of this research was confirmed and the objective achieved. However, future studies will be able to investigate how teachers autonomously apply these activities in the classroom and see if in fact children can, from practice, have a better understanding of the world with the technology around them and take ownership of new technological solutions and become possible active users. As a computer research, this project is part of the Computer Education area.